MINITUBERS PRODUCTION OF FOUR POTATO (SOLANUM TUBEROSUM L.) CULTIVARS BY TISSUE CULTURE TECHNIQUE - Toma, Rafail S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to produce potato minitubers via tissue culture technique by testing four cultivars; Agria, Nicola, SM 12-124-15 and JIP 1600-1 under in vitro, greenhouse and open-air field conditions. Nicola cultivar was superior upon the other cultivars under in vitro and greenhouse conditions by producing the best shoot multiplication (1.89 shoots/ explant and 13..27 leaves/ explant) and the highest number of minitubers (8.87 minitubers/ plant) in greenhouse whereas, SM 12-124-15 was better in the open field conditions by producing 11.25 tubers per plant, recording the highest mean weight of tubers (321.33 g), the highest weight of tubers per plant (3.615 kg), the bigger sizes of tubers (length 8.22 cm: width 3.43 cm) and the highest total yield per hectare (49.70 Ton/ ha). An interesting microtubers formation was noticed on SM 12-124-15 explants grown on MS medium supplemented with 0.5 mg/l-1 BA. The main conclusion drown from the current study is MS medium with basic vitamins and solidified by agar without the need of adding exogenous plant growth regulators can be used for mass seed tubers production based on potato genotype in vitro under optimized culture conditions with a low cost propagation system and shorter period of time than normal minitubers production process.